Current Principles of Treatment for Chronic Hematogenous Osteomyelitis in Children - Musayev Sodiqjon Toirovich (Journal of Science in Medicine and Life, 2024)
General information Classification Symptoms Causes Diagnosis Treatment Doctor's expert opinion Prevention Rehabilitation Question and answer Osteomyelitis in children is a pathological condition in which purulent damage is caused to all bone structures, as well as the bone marrow, along with the surrounding tissues. The disease in childhood is characterized by an acute onset, rapid development of symptoms and severe pain. Pediatricians, pediatric orthopedists-traumatologists, surgeons and other specialized specialists are involved in identifying the symptoms of bone osteomyelitis in children, searching for its causes and treating it. Most of the cases detected are between 6 and 14 years of age. At an early age, the main peak is observed in children under one year of age, and boys are twice as likely to have osteomyelitis than girls.